2019
DOI: 10.1021/jacs.9b05833
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Triggered Bioorthogonal Cleavage Reactions for Reversible Protein and Cell Surface Modifications

Abstract: Temporal and reversible control over protein and cell conjugations holds great potential for traceless release of antibody–drug conjugates (ADCs) on tumor sites as well as on-demand altering or removal of targeting elements on cell surface. We herein developed a bioorthogonal and traceless releasable reaction on proteins and intact cells to fulfill such purposes. A systematic survey of transition metals in catalyzing the bioorthogonal cleavage reactions revealed that copper complexes such as Cu­(I)-BTTAA and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 53 publications
(66 reference statements)
2
83
0
1
Order By: Relevance
“…For example, BCRs represent an efficient approach in cell engineering, such as in remodeling cell surface glycans, 127 unmasking the epitope of major histocompatibility complex class I (MHC-I), 128 , 129 and removing chemically labeled molecular probes. 41 More innovative applications in this direction will likely emerge in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, BCRs represent an efficient approach in cell engineering, such as in remodeling cell surface glycans, 127 unmasking the epitope of major histocompatibility complex class I (MHC-I), 128 , 129 and removing chemically labeled molecular probes. 41 More innovative applications in this direction will likely emerge in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has been interested in Cu due to the wide availability of biocompatible ligands owing to the broad applications of the CuAAC reaction in living systems. A systematic survey of the ligands and metals identified the Cu-2-[4-[[bis[(1- tert butyltriazol-4-yl)methyl]amino]methyl]triazol-1-yl] acetic acid (BTTAA)/disubstituted propargyl group as a new bioorthogonal cleavage pair, which facilitated the further extension of this chemistry from terminal to internal bond cleavage of the substituted propargyl scaffold 41 ( Figure 3 a, entries 20 and 21). In addition, a recent report by Bernardes et al utilized the Pt-triggered deprotection of pentynoyl or propargyl groups on amines for the release of MMAE and 5-FU 44 ( Figure 3 a, entry 22).…”
Section: Bcrs For Prodrug Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioorthogonal removal of O ‐propargyl and N ‐propargyloxycarbonyl groups can also be carried out with copper complexes. In particular, Chen and co‐workers have recently shown that the complex Cu I ‐BTTA, originally developed for azide–alkyne biocompatible cycloadditions, is also able to promote the bioorthogonal cleavage of O ‐propargyl and N ‐Poc groups that hold a second alkyl substituent at the propargylic position [131a] . The method constitutes the first examples of a copper‐catalyzed biorthogonal cleavage reaction and was applied to the release of drugs bearing a phenol or a primary amine moiety, such as the anticancer agent doxorubicin (Figure 51 A).…”
Section: Bond Cleavage Reactionsmentioning
confidence: 99%
“…By incorporating metals into nanoparticles or using homogeneous metal complexes to overcome the inherent cytotoxicity of the abiotic catalyst, several groups have demonstrated methods for metal‐based uncaging of drugs applicable in living systems. Employing metals like iron, palladium, copper, ruthenium, platinum and gold, several studies focused on release of amine/hydroxyl groups through protecting groups such as phenyl azide, [10] allyl, [11] propargyl, [12] allyloxycarbonyl, [13] dual‐substituted propargyloxycarbonyl, [14] 2‐alkynlbenzamide, [15] as well as a strategy based on ring‐closing metathesis [16] …”
Section: Introductionmentioning
confidence: 99%